Photoluminescence of Er-implanted GaN - Son, CS; Kim, S; Kim, YH; Han, IK; Kim, YT; Wakahara, A; Choi, IH; Lopez, HC (KOREAN PHYSICAL SOC, 2004)
Visible green emission has been observed from Er(Erbium)-doped GaN epilayers. Various doses of Er ions were implanted in GaN epilayers by using ion implantation. The optical properties of Er-doped GaN were analyzed by using photoluminescence (PL). Sharp emission lines due to inner 4f shell transitions for Er3+ were observed in the PL spectrum of Er-implanted GaN. The emission spectrum consisted of two narrow green lines, 537 and 558 nm. The green emission lines were identified as Er3+ transitions from the H-5(11/2) and the S-4(3/2) levels to the I-4(15/2) ground state. The stronger peaks in the 5 x 10(14) cm(-2) Sample, together with the relatively higher intensity of the Er3+ luminescence in the lower doped sample, indicate that some damage remains in the 1 x 10(15) cm(-2) sample.
Keywords: ELECTROLUMINESCENCE; EMISSION; LAYER; EU